Ontario’s Nursing Crisis Amidst the COVID-19 Pandemic and the Shift Away from Bedside Care: An Exploratory Study - Rowney, Rachel (Université d'Ottawa | University of Ottawa, 2026)
Ontario experienced a significant rise in nursing turnover during the COVID-19 pandemic, with many nurses leaving bedside care roles. This thesis explores the intentions and experiences of nurses in Ontario who left bedside nursing during the pandemic, focusing on the factors that shaped their decisions to leave as well as their considerations around returning to bedside practice. The study was conducted using an exploratory qualitative design guided by two theoretical frameworks, the Unfolding Model of Voluntary Employee Turnover (Lee & Mitchell, 1994) and the Job Embeddedness Model (Mitchell & Lee, 2001). Data was collected through semi-structured interviews with Ontario Registered Nurse participants (N = 4) who left bedside nursing during the pandemic. Interviews were thematically coded to analyze and systematically identify themes, patterns and insights. Three major themes emerged: 1) the Pandemic Exodus from Bedside Nursing, characterized by burnout and moral distress; 2) Rebuilding Bedside Nursing, emphasizing how leadership, mentorship, professional development and teamwork can support retention and re-entry to bedside practice; and 3) Redefining the Nursing Journey Beyond the Bedside, capturing nurses’ professional identity and the expanded career pathways within healthcare and the nursing profession. The findings illustrate the complex personal, professional and systemic factors that influenced Ontario nurses’ departure from the bedside during the pandemic. They highlight the need for targeted strategies that promote retention, re-entry and career sustainability to strengthen the nursing workforce post pandemic.
Keywords: Nursing; COVID-19; Pandemic